2013
DOI: 10.1371/journal.pone.0075502
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of FMRF-NH2 Peptides Demonstrate A Role for the Conserved C Terminus and Unique N-Terminal Extension in Modulating Cardiac Contractility

Abstract: FMRF-NH2 peptides which contain a conserved, identical C-terminal tetrapeptide but unique N terminus modulate cardiac contractility; yet, little is known about the mechanisms involved in signaling. Here, the structure-activity relationships (SARs) of the Drosophila melanogaster FMRF-NH2 peptides, PDNFMRF-NH2, SDNFMRF-NH2, DPKQDFMRF-NH2, SPKQDFMRF-NH2, and TPAEDFMRF-NH2, which bind FMRFa-R, were investigated. The hypothesis tested was the C-terminal tetrapeptide FMRF-NH2, particularly F1, makes extensive, stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…In the locust, for example, it appears that different receptors may respond to the FLRFamide peptides (particularly myosuppressins) in abdominal muscles than in muscles of the oviduct (Lange and Cheung 1999). In both Caenorhabditis elegans and Drosophila melanogaster, single neuropeptides, including those in the FMRFamide family, have been shown to activate two or more receptors; conversely, the same receptors are often activated by more than one related peptide, making for complex signaling possibilities (Johnson et al 2003;Klose et al 2010;Li 2005;Maynard et al 2013). Among the most intriguing of these studies is that by Klose et al (2010), demonstrating that two receptors are required for enhancement at the NMJ in a larval Drosophila muscle.…”
Section: Factors Determining Contraction Frequencymentioning
confidence: 99%
“…In the locust, for example, it appears that different receptors may respond to the FLRFamide peptides (particularly myosuppressins) in abdominal muscles than in muscles of the oviduct (Lange and Cheung 1999). In both Caenorhabditis elegans and Drosophila melanogaster, single neuropeptides, including those in the FMRFamide family, have been shown to activate two or more receptors; conversely, the same receptors are often activated by more than one related peptide, making for complex signaling possibilities (Johnson et al 2003;Klose et al 2010;Li 2005;Maynard et al 2013). Among the most intriguing of these studies is that by Klose et al (2010), demonstrating that two receptors are required for enhancement at the NMJ in a larval Drosophila muscle.…”
Section: Factors Determining Contraction Frequencymentioning
confidence: 99%
“…Greenberg & Price, 1992;Lange, 2001;Mercier, Friedrich, & Boldt, 2003). In Drosophila, they are implicated in cardiac function, locomotion, flight, ecdysis and stress-induced sleep (Agrawal, Sadaf, & Hasan, 2013;Kim et al, 2006;Klose, Dason, Atwood, Boulianne, & Mercier, 2010;Lenz, Xiong, Nelson, Raizen, & Williams, 2015;Maynard et al, 2013;Taghert, 1999). The dFMRFa gene (Nambu et al, 1988;Schneider & Taghert, 1988) encodes eight distinct peptides, five of which contain the amidated C-terminal sequence FMRFamide and three with sequences similar to FMRFamide (SAPQDFVRSamide, MDSNFIRFamide and SVQDNFMHFamide).…”
Section: Fmrfamidesmentioning
confidence: 99%
“…Thus, many people have favoured the view that there is only one receptor for the peptides encoded in dFMRFa, at least at physiologically relevant peptide concentrations. Receptor and ligand modeling indicates that the five Drosophila peptides containing the sequence 'FMRFamide' exhibit subtle differences in docking and linking with the FMRFamide receptor, but they all elicit very similar responses in cardiac bioassays (Maynard et al, 2013). Hewes et al (1998) also found that DPKQDFMRFamide increases synaptic current in muscle fiber 6, indicating increased transmitter release from presynaptic axons.…”
Section: Fmrfamidesmentioning
confidence: 99%
“…Myosuppressins are members of a family of peptides with an identical C-terminal RF-NH 2 , however, the N-terminal extension is unique and differs in length and sequence [ 4 ]. The identical C terminus and variant N terminus are both important in binding and activating signaling pathways [ 5 , 6 ]. FMRF-NH 2 , the first RF-NH 2 -containing peptide isolated, was identified from a neural extract applied to a clam heart preparation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%